Spontaneous hemopneumothorax - Brandolino, Mario V; Nin Vivo, Jorge; Sanjinés, Aníbal (Cirugía del Uruguay, 1985)
Study of 15 spontaneous hemopneumoyhorax: 14 men and one woman. Consideration of pathological aspects, clinical and radiological characteristics. Stressed are the necessity of urgen! pleural draining and the strict clinical and radiological control, also emphasi• zing the necessity of early thoracotomy in case of per• sistent active bleeding or a residual coaguloma. The object of the surgical treatment is the hemostasis, connection of emphysema vesicles also provoking a pleurodesis by pleural abrasion.